Cryptic speciation and recombination in the fungus Paracoccidioides brasiliensis as revealed by gene genealogies - Matute, D. R.; McEwen, J. G.; Montes, B. A.; San-Blas, G.; Bagagli, E.; Rauscher, J. T.; Restrepo, A.; Morais, F.; Nino-Vega, G.; Taylor, J. W. (Oxford University Press, 2006)
Paracoccidioides brasiliensis is the etiologic agent of paracoccidioidomycosis, a disease confined to Latin America and of marked importance in the endemic areas due to its frequency and severity. This species is considered to be clonal according to mycological criteria and has been shown to vary in virulence. To characterize natural genetic variation and reproductive mode in this fungus, we analyzed P. brasiliensis phylogenetically in search of cryptic species and possible recombination using concordance and nondiscordance of gene genealogies with respect to phylogenies of eight regions in five nuclear loci. Our data indicate that this fungus consists of at least three distinct, previously unrecognized species: S1 (species 1 with 38 isolates), PS2 (phylogenetic species 2 with six isolates), and PS3 (phylogenetic species 3 with 21 isolates). Genealogies of four of the regions studied strongly supported the PS2 clade, composed of five Brazilian and one Venezuelan isolate. The second clade, PS3, composed solely of 21 Colombian isolates, was strongly supported by the alpha-tubulin genealogy. The remaining 38 individuals formed S1. Two of the three lineages of P. brasiliensis, S1 and PS2, are sympatric across their range, suggesting barriers to gene flow other than geographic isolation. Our study provides the first evidence for possible sexual reproduction in P. brasiliensis S1, but does not rule it out in the other two species.
Keywords: phylogenetic species; cryptic speciation; recombination; Paracoccidioides brasiliensis